Mustahiq (Zakat Recipient) Determination Application with Analytic Hierarchy Process Model - Husein, Ismail; Zein, Achyar; Sabrina, Ladia (Politeknik Ganesha Medan, 2022)
. Zakat is a rule in Islam and is included in the third pillar of Islam related to property. Zakat has a purpose, namely to clean our wealth and zakat can cleanse the human heart from greed, miserliness, and worldly nature. Zakat also helps the implementation of social security programs by balancing the status between communities, so that there is no social inequality that is too far in the gap between rich and poor. Zakat processing must be managed as well as possible by the amil zakat agency, which is currently the institution that manages zakat, namely the National Amil Zakat Agency (BAZNAS). Therefore, to achieve this goal, BAZNAS must be able to determine which parties are entitled to receive zakat, so that it is right on target.This study aims to determine the determination of mustahiq by applying the application through the analytic hierarchy process (AHP) model.The results obtained in this study contained five criteria modeled in the analytic hierarchy process (AHP). The main criteria factors that influence the determination of mustahiq are the criteria for workers with a result of 49.5%, then the second factor that affects is the number of dependents of the family who get a result of 24.1%, after that the third factor that influences is income (income) with a result of 16.6 %, then the fourth factor is home ownership with a yield of 6.1% and the last factor, namely age, has a result of 3.4%.